A LEVEL-SET CORRECTOR TO AN ADAPTIVE MULTISCALE PERMEABILITY PREDICTION - Berre I.; Lien M.; Mannseth T. (My University, 2007)
We consider the inverse problem of permeability estimation for two-phase porous-media flow. The novel approach is based on regularization by zonation, where the geometry and size of the regions are chosen adaptively during the optimization procedure. To achieve this, we have utilized level-set functions to represent the permeability. The available data are sparsely distributed in space; hence, it is reasonable to confine the estimation to coarse-scale structures. The level-set approach is able to alter the boundaries between regions of different permeability without strict restrictions on their shape; however, when the data are sparse, a reasonable initial guess for the permeability is required. For this task, we use adaptive multiscale permeability estimation, which has the potential of identifying main permeability variations. These are described by a piecewise constant function, where the constant values are attained on rectangular zones. In the current work, we develop a level-set corrector strategy, assuming adaptive multiscale permeability estimation as a predictor.
Keywords: ADAPTIVE MULTISCALE ESTIMATION; INVERSE PROBLEM; LEVEL-SET REPRESENTATION; PERMEABILITY ESTIMATION; REGULARIZATION; TWO-PHASE FLOW